The effect of disinfectants and antiseptics on co- and cross-selection of resistance to antibiotics in aquatic environments and wastewater treatment plants - Basiry, Daniel; Entezari Heravi, Nooshin; Uluseker, Cansu; Kaster, Krista Michelle; Kommedal, Roald; Pala-Ozkok, Ilke (Frontiers in Microbiology, 2022)
The outbreak of the SARS-CoV-2 pandemic led to increased use of disinfectants and antiseptics (DAs), resulting in higher concentrations of these compounds in wastewaters, wastewater treatment plant (WWTP) effluents and receiving water bodies. Their constant presence in water bodies may lead to development and acquisition of resistance against the DAs. In addition, they may also promote antibiotic resistance (AR) due to cross- and co-selection of AR among bacteria that are exposed to the DAs, which is a highly important issue with regards to human and environmental health. This review addresses this issue and provides an overview of DAs structure together with their modes of action against microorganisms. Relevant examples of the most effective treatment techniques to increase the DAs removal efficiency from wastewater are discussed. Moreover, insight on the resistance mechanisms to DAs and the mechanism of DAs enhancement of cross- and co-selection of ARs are presented. Furthermore, this review discusses the impact of DAs on resistance against antibiotics, the occurrence of DAs in aquatic systems, and DA removal mechanisms in WWTPs, which in principle serve as the final barrier before releasing these compounds into the receiving environment. By recognition of important research gaps, research needs to determine the impact of the majority of DAs in WWTPs and the consequences of their presence and spread of antibiotic resistance were identified.